The Effect of Competence Human Resources, Implementing Commitments, Implementation of Regulation and Quality of Training on Compliance with Government Regulation Number 71 of 2010 Regarding Fixed Assets - Dri Asmawanti-S (AFEBI Accounting Review, 2020)
This study aims to test and prove the influence of human resource competencies, implementing commitments, implementing regulations, and the quality of training on compliance with government regulation number 71 of 2010 regarding fixed assets. The population in this study were all financial management apparatus in the Regional Devices Organization in the City Government of Bengkulu. The data used in this study are primary data, which was obtained by distributing questionnaires to the respondents. The sample in this study amounted to 146 respondents, data analysis was performed using SPSS version 22. Hypothesis testing used multiple linear analysis. The results showed that the competence of human resources, implementing commitment, the application of regulations, and the quality of training proved to have a positive effect on compliance with government regulation number 71 of 2010 regarding fixed assets.